First report of Sciopemyia vattierae (Le Pont & Desjeux, 1992) (Diptera, Psychodidae) from states of Amazonas and Pará, northern Brazil - Salvador Paganella Chaves Júnior; Lara Cássen de Souza Santos; Kennedy Alves de Oliveira; Diomar Coutinho de Barros; Marcos Miranda de Almeida; Paloma Helena Fernandes Shimabukuro; Eunice Aparecida Bianchi Galati; Israel de Souza Pinto (Check List)
This study reports the first records of Sciopemyia vattierae (Le Pont & Desjeux, 1992) in the Brazilian states of Amazonas and Pará. In Amazonas, specimens were collected from the Hi-Merimã and Paumari do Lago Marahã indigenous lands (municipalities of Tapauá and Lábrea, respectively), and the Urucu River region (Coari). In Pará, collections were made within the Amazon National Park (Itaituba). Specimens were captured using various traps between 2011 and 2023. These findings support the hypothesis that S. vattierae is an Andean and cis-Andean species.